519PInitial results of lung cancer genomic screening project for individualized medicine in Asia: LC-SCRUM-Asia. (24th November 2019) - Kuo, C-H S; Yoh, K; Yang, C-T; Wang, C-C; Yen, T-C; Lin, K-J; Ikeda, T; Zenke, Y; Matsumoto, S; Goto, K
Abstract: Background: LC-SCRUM was established in 2013 to screen target genes in lung cancer to advance the development of new molecular targeted drugs and diagnostics. To date, with the cooperation of over 200 institutions across Japan, LC-SCRUM has performed genomic analysis of over 7000 lung cancer patients. Since Mar 2019, LC-SCRUM has expanded to Taiwan as genomic screening infrastructure with the cooperation of Asian countries. Here, we report initial results of Asian international genomic screening, LC-SCRUM-Asia. Methods: Tumor samples of non-small cell lung cancer patients were analyzed for oncogenic alterations using targeted next-generation sequencing (NGS) with Oncomine Comprehensive Assay. The analysis was performed as central test at CLIA lab in Japan. Results: As of May 31th in 2019, the LC-SCRUM-Asia has the participation of 5 institutions in Taiwan and 161 in Japan. For the first 2 month, a total of 477 patients (23 from Taiwan and 454 from Japan) were enrolled in this study. Median age were 68 years (range, 45-84) in Taiwan cohort and 67 (28-87) in Japan. In Taiwan 65% of patients were women, 70% adenocarcinoma and 70% non-smoker, and in Japan 37% of patients were women, 79% adenocarcinoma and 29% non-smoker, respectively. Of 13 analyzable patients in Taiwan, targeted NGS showed that 9 (69%) had at least one targetable oncogenic alterations, including 4 EGFR mut, 2 KRAS mut, 2 ALK fusinos and 1 RET fusions plus EGFR mut. Of 423 patients in Japan, 196 (46%) had at least one targetable oncogenic alterations. Oncogenic alterations commonly found were EGFR mut (19%), KRAS mut (13%), ALK fusions (2%), RET fusions (1%) and others in Japan. Conclusions: Asian international genomic screening can be implemented between Taiwan and Japan settings. LC-SCRUM-Asia will contribute to further development of precision medicine for lung cancer patients in Asia. Updated results will be presented at the meeting. Legal entity responsible for the study: LC-SCRUM-Asia. Funding: AstraZeneca, Ignyta, Kyowa Hakko Kirin, Daiichi Sankyo, Eisai, Taiho, Takeda, Merck Serono, Novartis, MSD, Pfizer, Lilly, Bristol-Myers Squibb, Chugai, Boehringer Ingelheim, Astellas, LOXO, Janssen, Thermo Fisher Scientific, Ono. Disclosure: C-H.S. Kuo: Honoraria (self): AstraZeneca; Honoraria (self), Advisory / Consultancy: Boehringer Ingelheim; Honoraria (self): Roche; Honoraria (self): Pfizer; Honoraria (self): Eli Lilly; Honoraria (self), Advisory / Consultancy: Novartis; Honoraria (self): ONO Pharma; Honoraria (self), Advisory / Consultancy: Merck; Advisory / Consultancy: Chugai; Advisory / Consultancy: Takeda. K. Yoh: Honoraria (self): Chugai; Honoraria (self), Research grant / Funding (institution): AstraZeneca; Honoraria (self), Research grant / Funding (institution): Lilly; Research grant / Funding (institution): Bayer; Research grant / Funding (institution): Pfizer; Research grant / Funding (institution): Taiho; Research grant / Funding (institution): MSD; Honoraria (self): Novartis. Y. Zenke: Honoraria (self): Boehringer Ingelheim; Honoraria (self): AstraZeneca; Honoraria (self): Lilly; Honoraria (self): Chugai; Honoraria (self), Research grant / Funding (institution): MSD; Honoraria (self): Taiho; Honoraria (self): Ono pharmaceutical. S. Matsumoto: Honoraria (self): AstraZeneca; Honoraria (self), Research grant / Funding (institution): Novartis; Honoraria (self): Pfizer; Honoraria (self), Research grant / Funding (institution): Lilly; Research grant / Funding (institution): Merck Serono; Research grant / Funding (institution): MSD; Honoraria (self), Research grant / Funding (institution): Chugai Pharma. K. Goto: Honoraria (self), Research grant / Funding (institution): AstraZeneca; Honoraria (self), Research grant / Funding (institution): Lilly; Honoraria (self), Research grant / Funding (institution): Chugai; Research grant / Funding (institution): Ignyta; Research grant / Funding (institution): Kyowa Hakko Kirin; Research grant / Funding (institution): Daiichi Sankyo; Research grant / Funding (institution): Eisai; Research grant / Funding (institution): Taiho; Research grant / Funding (institution): Takeda; Research grant / Funding (institution): Merck Serono; Research grant / Funding (institution): Novartis; Research grant / Funding (institution): MSD; Research grant / Funding (institution): Pfizer; Research grant / Funding (institution): Bristol-Myers Squibb; Research grant / Funding (institution): Boehringer Ingelheim; Research grant / Funding (institution): Astellas; Research grant / Funding (institution): LOXO; Research grant / Funding (institution): Janssen; Research grant / Funding (institution): Thermo Fisher Scientific; Research grant / Funding (institution): Ono. All other authors have declared no conflicts of interest.